The relationship between marketing mix, healthy lifestyle and the consumption patterns of healthy food among Malaysian consumers - Djermani, Farouk (2020)
Unhealthy food consumption has been linked to the risk of many diseases such as noncommunicable diseases and obesity. Thus, this study aimed to examine the effects of marketing mix dimensions (product, price, promotion, and place) on the consumption patterns of healthy food and healthy lifestyle as well as to examine the mediating effects of healthy lifestyle between the specified linkages. A quantitative research design approach was selected where the questionnaire was formulated for primary data collection. The variables were measured using 33 items sourced from past studies. All the items were assessed using the five-point Likert scale. 500 questionnaires were distributed to academicians from four Universities (UUM, UniMap, UPSI, USM) by using the random sampling technique. 357 responses were returned, representing a 71.4% response rate. The analysis method used the partial least square (PLS 3) regression and descriptive methods. The findings indicate that consumer healthy lifestyle, promotion and place are positive and significant predictors of consumption patterns while product, price, and promotion are significant predictors of a consumer healthy lifestyle. The results of the mediation effects of a healthy lifestyle show that healthy lifestyle is a significant mediator between product, price, and promotion with consumption patterns. As Malaysian consumers exhibit serious concern towards healthy food consumption patterns, it is recommended that the managers focus their strategies on promotion and place more significance on healthy lifestyle in their healthy food consumption patterns. The study discusses the implications to various stakeholders, its limitation and recommendations for future studies.